ANALISIS PENGARUH FAKTOR-FAKTOR EKONOMI MAKRO TERHADAP IHSG DI BURSA EFEK INDONESIA (BEI) - Dian Surya Sampurna Sampurna (Jurnal Ekonomi, 2016)
The purpose of this research was to analyze the effects of SBI interest rate and exchange rate of rupiah against JCI. This research using secondary data from the monthly during the period Januari 2008 to December 2015 and the data source from www.finance.yahoo.com and www.bi.go.id. This research used multiple linear regression analysis method. The results showed that SBI interest rate and exchange rate of rupiah had negative effect on JCI. Simultaneously SBI interest rate and exchange rate of rupiah has significant influence on JCI. Adjusted R2 value of 0.586 indicates that the independent variables used in the study has contributed to the establishment of JCI amounted to 58.6%, while 41.4% drawbacks established by other variables outside the research model.